In Vitro Fracture Strength of Primary Canine Teeth Reinforced With Prefabricated and Customized Fiber‐Reinforced Post Systems - Faeze Behzadpour; Nilgoon Pasdar; Ghazaleh Ahmadizenouz; Ali Bijani (Wiley, 2024)
Abstract Objective The demand for esthetics has increased in today's world and most parents prefer to preserve their children's primary anterior teeth until their natural exfoliation. However, an intracanal post is required to provide retention for reconstruction of severely damaged anterior teeth due to caries or trauma. Various materials and methods may be used for the fabrication of intracanal posts. This study assessed the fracture strength and fracture mode of primary canine teeth reconstructed with prefabricated and customized polyethylene and glass fiber posts. Materials and Methods This in vitro study evaluated 60 extracted primary canine teeth in four groups (n = 15). After pulpectomy and post space preparation with 4 mm depth, composite resin post, prefabricated glass fiber post (Whitepost), customized glass fiber post (Interlig), or customized polyethylene fiber post (Ribbond) were placed in the root canals to provide retention, and the tooth crown was restored with bulk‐fill composite resin. The fracture strength was then measured in a universal testing machine. The fracture mode was also evaluated visually. Results The mean fracture strength was 22.45 ± 5.06, 33.10 ± 8.5, 30.20 ± 7.33, and 32.61 ± 5.73 N/mm2 in the composite resin post, Whitepost, Interlig, and Ribbond groups, respectively. The fracture strength was significantly lower in the composite group than in the remaining three groups (p = 0.000). No other significant differences were found (p > 0.05). Also, no significant difference was observed among the study groups in the fracture mode (p = 0.241). Conclusion The composite resin post yielded a significantly lower fracture strength than the prefabricated and customized glass and polyethylene fiber posts, but the fracture mode was not significantly different among the four groups.